KNOWLEDGE AND ATTITUDE AMONG RESIDENT DOCTORS RELATED TO ETHICAL AND MEDICOLEGAL ISSUES IN A TEACHING HOSPITAL - Taufik Suryadi Ismail; Kulsum Kulsum (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Ethics and medicolegal as a mandatory competence that must be applied by resident doctors, because it is very helpful of deciding on medical practice. This study aims to assess the current status of the knowledge and attitude of dealing with ethical and medicolegal issues among resident doctors in a teaching hospital in Aceh.Methods: This was a cross-sectional study conducted among resident doctors (n=156) with a self-administered online questionnaire. The Spearman test was used to identify the correlation between knowledge and attitudes. Meanwhile, the Chi-square test was used to identify the significance of influence selected factors with knowledge and attitude.Results: A total of 156 respondents were involved in this study. Most resident doctors (94.2%) had limited knowledge and as many as 66% have a positive attitude in dealing with ethical and medicolegal issues. Based on the Spearman's and Chi-square test showed not a significant correlation between the knowledge and attitudes under the Sig. (2-tailed) 0.086 (Sig. (2-tailed) >0.05) and p-value 0.296 (p-value >0.05). Only length of education was significantly associated with a positive level of attitude (p=0.003). Selected factors did not significantly affect the lack of knowledge, for gender with a p-value of 1.000, age (p=0.306), study program (p=0.192), and length of education (p=1.000).Conclusion: Positive attitudes are a very valuable asset to increase knowledge in dealing with ethical and medicolegal issues. The lack of knowledge of resident doctors is influenced by various factors. It is necessary to increase knowledge through continuing education, regular training, and short courses.